Advances in nanotechnology for cancer biomarkers. (February 2018) - Ye, Fei; Zhao, Ying; El-Sayed, Ramy; Muhammed, Mamoun; Hassan, Moustapha
Graphical abstract: Highlights: Nanoparticle-assisted early detection of cancer biomarkers is summarized. Nanoparticle conjugation methods and biomolecule targeting strategies are discussed. Investigation of recent developments in cancer biomarker nanosensing strategies. Nanotechnology in mass spectrometry, optical, electrical and electrochemical assays. Nanotechnology as a tool to enhance biomarker detection sensitivity and specificity. Abstract: Cancer biomarkers with high selectivity, specificity and reproducibility play essential role in diagnosis, prognosis and prediction of treatment efficacy in cancer patients. However, the current biomarker assays used in clinics could be improved due to low sensitivity and specificity. Nanoparticle-based assays are emerging as an upcoming approach, providing ultra-high sensitivity and specificity in cancer biomarker detection. The current survey presents an overview of strategies used in the development and integration of nanoparticles for cancer biomarker detection, including mass spectrometry, optical and electrical detection methods. Moreover, we discuss the future trends in the field in correlation to new approaches from fundamental and practical standpoints.